Creativity Of Pancasila Education Teachers and Citizens in Making Learning Media - Rabiatul Adawiah; Dian Agus Rochliydi; Taufik Hidayat (JED (Jurnal Etika Demokrasi), 2022)
Based on observations of Pancasila and Citizenship Education teachers in secondary schools, almost all of the learning media used rely on those already available in schools. However, in contrast to the Pancasila and Citizenship Education teachers in general, the Pancasila and Citizenship Education teachers at SMP Negeri 2 Kusan Hilir are very creative teachers to make various learning media, so that many achievements have been achieved both at the regional and provincial levels.This study aims to determine the creativity of teachersPancasila and civic educationin making learning media and knowing students' interest in participating in learningPancasila and civic education. This research is a qualitative research with descriptive method. Data was collected by using interview, observation and documentation techniques. The data obtained were analyzed qualitatively with the stages of data collection (data collection), data reduction (data reduction), data presentation (data display), and drawing conclusions or verification (conclusions). From this study it can be concluded that teachersPancasila and civic educationat the State Junior High School 2 Kusan Hilir, Tanah Bumbu Regency is very creative in making learning media. Some of the learning media that have been created include: Child Moral Control Tree (Pokemon), traditional Banjar Batewah game media, constitution-themed song media, ethnic diversity media through used newspapers, and picture guessing media. Implementation of learningPancasila and civic educationwith a variety of media makes students more interested and motivated to take part in learning.